2015
DOI: 10.1111/hepr.12559
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hepatitis without hepatic steatosis caused by citrin deficiency in a child

Abstract: Citrin deficiency manifests as both neonatal intrahepatic cholestasis (NICCD) during early infancy and adult-onset type II citrullinemia during adulthood. Hepatic steatosis is most frequently observed in patients with citrin deficiency. Thus, non-alcoholic fatty liver disease that is unrelated to being overweight is considered one of the clinical features of citrin deficiency in children and adults. However, it remains unknown whether citrin deficiency is a cause of chronic hepatitis in the absence of fatty ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…CTLN2 is the adult-onset hyperammonemic encephalopathy form of CD in which a variety of hepatic involvements have been reported. ALF was reported in an 8-year-old girl without encephalopathy (Inui et al 2015). Similar histological patterns as NICCD have been described, with micro-and macrovesicular steatosis ( (Tanaka et al 2002(Tanaka et al , 2007.…”
Section: Ctln2supporting
confidence: 66%
“…CTLN2 is the adult-onset hyperammonemic encephalopathy form of CD in which a variety of hepatic involvements have been reported. ALF was reported in an 8-year-old girl without encephalopathy (Inui et al 2015). Similar histological patterns as NICCD have been described, with micro-and macrovesicular steatosis ( (Tanaka et al 2002(Tanaka et al , 2007.…”
Section: Ctln2supporting
confidence: 66%
“…However, detailed information on the genetic mutations, symptoms, and outcomes was not available [ 2 ]. Inui et al [ 3 ] described an 8-year-old girl with an SLC25A13 mutation who showed no fatty changes of the liver by light microscopy. In this patient, very small fatty droplets were observed by electron microscopy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…While we did not analyze the mechanism of the latent appearance of overt clinical features of CTLN2 in our patient, it is possible that such a phenotype is more likely to be seen in females than males, based on a possible gender difference in resistance to the onset of CTLN2 and the suppression of fat deposition in the liver. In this regard, Inui et al (20) also reported an 8-year-old girl with CTLN2 who presented with chronic hepatitis without hepatic steatosis.…”
Section: Discussionmentioning
confidence: 95%